EVELIO B. JAVIER: AWARENESS OF THE YOUNG GENERATION ABOUT THEIR LOCAL HERO - Leila May S. Navas (International Conference on Social and Islamic Studies, 2021)
Modern day heroes are rare. If there is one locally, this person will always be a study incontrast. With many people knowing and having made an interaction with the person it isexpected that the person will be described in a way in which all his virtues and flaws will begiven. This descriptive study sought to determine the level of awareness of the young generation about their local hero Evelio B. Javierand to develop learning materials about the lifeof the local hero Evelio B. Javier. The 526 respondents of the study in the level of awarenessare the Grade 8 students from selected private and public secondary schools in the Division of Antique randomly selected through stratified random sampling. Standard deviation and meanswere employed for the descriptive analysis of the study. The t-test and One-way ANOVA wereused for inferential analysis. The respondents of the study exhibited a slight awareness level interms of their knowledge about the life of Evelio B. Javier. When the respondents were groupedbased on the schools where they were enrolled the three groups exhibited no significantdifference on their means. This means that regardless of what school the students wereenrolled the responses of the respondents will be statistically the same. Regardless of sex andschool where they are enrolled, anybody can have the full potential to be aware of the life ofthe local hero Evelio B. Javier.